Nano–bio surface interactions, cellular internalisation in cancer cells and e‐data portals of nanomaterials: A review - Ram Dhan Yadav; Abha Chaudhary (IET Nanobiotechnology)
Abstract Nanomaterials (NMs) have abundant applications in areas such as electronics, energy, environment industries, biosensors, nano devices, theranostic platforms, etc. Nanoparticles can increase the solubility and stability of drug‐loaded materials, enhance their internalisation, protect them from initial destruction in the biological system, and lengthen their circulation time. The biological interaction of proteins present in the body fluid with NMs can change the activity and natural surface properties of NMs. The size and charge of NMs, properties of the coated and uncoated NMs, nature of proteins, cellular interactions direct their internalisation pathway in the cellular system. Thus, the present review emphasises the impact of coated, uncoated NMs, size and charge, nature of proteins on nano–bio surface interactions and on internalisation with specific focus on cancer cells. The increased activity of NPs may also result in toxicity on health and environment, thus emphasis should be given to assess the toxicity of NMs in the medical field. The e‐data sharing portals of NMs have also been discussed in this review that will be helpful in providing the information about the chemical, physical, biological properties and toxicity of NMs.